Flightless I Alters the Inflammatory Response and Autoantibody Profile in an OVA-Induced Atopic Dermatitis Skin-Like Disease - Kopecki, Zlatko; Stevens, Natalie E.; Chong, Heng T.; Yang, Gink N.; Cowin, Allison J. (Frontiers in Immunology, 2018)
Atopic dermatitis (AD) is a chronic pruritic inflammatory skin disease characterized by excessive inflammation and disrupted skin barrier function. Although the aetiology of AD is not completely understood, clinical and basic studies suggest increasing involvement of autoantibodies against intracellular proteins. An actin remodelling protein, Flightless I (Flii), has been shown to promote development of inflammatory mediated skin conditions and impairment of skin barrier development and function. Here we sought to determine the effect of altering Flii expression on the development of AD and its contribution to autoimmune aspects of inflammatory skin conditions. Ovalbumin (OVA)-induced AD skin-like disease was induced in Flii heterozygous (Flii+/-), wild-type (Flii+/+) and Flii transgenic (FliiTg/Tg) mice by epicutaneous exposure to OVA for 3 weeks; each week was separated by 2-week resting period. Reduced Flii expression resulted in decreased disease severity and tissue inflammation as determined by histology, lymphocytic and mast cell infiltrate and increased anti-inflammatory IL-10 cytokine levels and a marked IFN-γ Th1 response. In contrast, Flii over-expression lead to a Th2 skewed response characterised by increased pro-inflammatory TNF-α cytokine production, Th2 chemokine levels and Th2 cell numbers. Sera from OVA-induced AD skin-like disease Flii+/- mice showed a decreased level of autoreactivity while sera from FliiTg/Tg mice counterparts showed an altered autoantibody profile with strong nuclear localization favouring development of a more severe disease. These findings demonstrate autoimmune responses in this model of OVA-induced AD-like skin disease and suggest that Flii is a novel target, whose manipulation could be a potential approach for the treatment of patients with AD.